Kondisi Mediatisasi Kontemporer Agama Pada Status Kritis Dan Arah Masa Depan - Magdalena Pura Bandaso; Kristiani Ela; Janto; Mikael Palittin; Joice Alfista Karru (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2022)
Over the last decade the mediatization theoretical framework has been introduced in the fields of media, religion and culture as a parallel perspective to the “religious mediation” approach, which allows new questions to be raised in line with the changing religion in Indonesia. This article provides a critique of existing research applying religious mediation theory, focusing on the key issues raised by its proponents and how the theory has advanced research. These issues concern the concept of religion, institutions and social change, religious authority, and the application of mediatization theory outside the Indonesian context. The article argues that the institutional approach to mediation is a relevant tool for analyzing change as a dynamic process in which the logic of certain forms of media influences practices, values, and relationships in particular types of analysis.